PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, INVESTMENT OPPORTUNITY SET DAN PROFITABILITAS PADA KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR - Yudiana, I Gede Yoga; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
This study is an empirical study to test the effect of managerial ownership variable, leverage, investment opportunity set, and profitability on the dividend policy as measured by dividend payout ratio of manufacturing companies listed in Indonesia Stock Exchange with the observation period 2011-2013. Determination samples using purposive sampling technique through certain criteria in order to obtain a sample of 126 companies of observation. The analysis technique used in this research is multiple linear regression and hypothesis testing using t-statistic to test the partial regression coefficient and f-statistic to test the feasibility of the research model with a level of significance of 5%. It also made the classic assumption test including normality test, multicolinearity test, test and test heteroskedastisitas autokorelasi. The result analysis shows that managerial ownership has no effect on dividend policy, while leverage and investment opportunity set negative effect on dividend policy, as well as a positive effect on profitability dividend policy.
Keywords: dividend policy, managerial ownership, leverage, investment opportunity set, profitability